Lapis Sari Bakery and Cake Shop / Imran Adib Azman … [et.al.]. - Azman, Imran Adib; Sauluhin, Shahisnawi; Abdul Rahim, Muhammad Zharif Iqbal; Zaidel, Aidah; Kok, Nadiatul Izzah (2019)
Lapis Sari is recognized by many people all over Malaysia especially in Kuching, Sarawak where it is basically based in. Lapis Sari is a family owned bakery and cake shop and is managed by an optimist, wise and smart woman, Puan Sharifah Noralami. We admire her passion and her standards in making excellent quality products for her customers. We believed that is how she can maintained to be one of the best selling Kek Lapis in Malaysia.